Penegakan Hukum Terhadap Tindak Pidana Pencurian : Studi Putusan Nomor 1382/Pid.B/2023/PN Medan - Citra Situmorang; Gerry Frizi Jonatan Manalu; Sella Ariska; Parlaungan Gabriel Siahan; Dewi Pika Lumban Batu (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This research discusses how to enforce the law against criminal acts of theft. This research is a case study research using a normative juridical approach. The normative juridical approach is a method of research carried out by studying the main legal materials such as theories, concepts, legal principles and statutory regulations related to this research. The results of the research show that the acts of theft that occurred have been carried out repeatedly so that this criminal act is a recidivist crime. The Criminal Code has regulated it and must be carried out by law enforcers who implement these regulations, as an embodiment of what is regulated in the Criminal Code. In efforts to enforce the law against criminal acts of theft, especially recidivism, it is necessary to implement the things that have been included in the statutory regulations, so that a sense of security, comfort and peace can be created in the environment and relationships within the family and social community. There are several factors that influence these crimes, including internal factors, external factors and economic factors.